Cigarette Cravings, Impulsivity, and the Brain - Potvin, Stéphane; Tikàsz, Andràs; Dinh-Williams, Laurence Lê-Anh; Bourque, Josiane; Mendrek, Adrianna (Frontiers in Psychiatry, 2015)
Craving is a core feature of tobacco use disorder as well as a significant predictor of smoking relapse. Studies have shown that appetitive smoking-related stimuli (e.g. someone smoking) trigger significant cravings in smokers which impedes their self-control capacities and promotes drug seeking behavior. In this review, we begin by an overview of functional magnetic resonance imaging (fMRI) studies investigating the neural correlates of smokers to appetitive smoking cues. The literature reveals a complex and vastly distributed neuronal network underlying smokers’ craving response that recruits regions involved in self-referential processing, panning/regulatory processes, emotional responding, attentional biases, and automatic conducts. We then selectively review important factors contributing to the heterogeneity of results that significantly limit the implications of these findings, namely between- (abstinence, smoking expectancies and self-regulation) and within-studies factors (severity of smoking dependence, sex-differences, motivation to quit and genetic factors). Remarkably, we found that little to no attention has been devoted to examine the influence of personality traits on the neural correlates of cigarette cravings in fMRI studies. Impulsivity has been linked with craving and relapse in substance and tobacco use, which prompted our research team to examine the influence of impulsivity on cigarette cravings in an fMRI study. We found that the influence of impulsivity on cigarette cravings was mediated by fronto-cingular mechanisms. Given the high prevalence of cigarette smoking in several psychiatric disorders that are characterized by significant levels of impulsivity, we conclude by identifying psychiatric patients as a target population whose tobacco smoking habits deserve further behavioral and neuro-imaging investigation.